دور الوقف في تحقيق التنمية الاقتصادية والاجتماعية - لمسلف,عبلة (University of Eloued جامعة الوادي, 2024)
Abstract: This research aims to identify the role of the waqf in achieving economic and social development in Constantine, based on the descriptive analytical approach, we concluded that the waqf in Constantine play a significant role in achieving economic and social development, however, it still suffers from several challenges. We recommend the necessity of inventorying, retrieving and documenting the waqf properties in Constantine, and developing policies that contribute to investing them through various forms of Islamic investment, especially sukuk of waqf, In addition to enhancing the decentralization of the waqf organizations by digitizing administration of the waqf.ملخص: يهدف هذا البحث إلى التعرف على دور الوقف في تحقيق التنمية الاقتصادية والاجتماعية، مع تسليط الضوء على حالة ولاية قسنطينة، بالاعتماد على المنهج الوصفي التحليلي، وتوصلنا إلى أن أوقاف قسنطينة تؤدي دورا معتبرا في تحقيق التنمية الاقتصادية والاجتماعية، إلا أنها لا تزال تعاني من عدة تحديات تعيق أداءها للدور التنموي المنوط بها. وعليه نوصي بضرورة حصر واسترجاع وتوثيق الأملاك الوقفية في ولاية قسنطينة، وتطوير السياسات التي تساهم في استثمارها من خلال مختلف صيغ الاستثمار الإسلامي ولا سيما الصكوك الوقفية، بالإضافة إلى تعزيز لا مركزية الهيئات الوقفية عن طريق رقمنة الإدارة الوقفية.
دراسة حالة ولاية قسنطينة
Keywords: الوقف; التنمية; الاقتصادية; الاجتماعية; waqf; development; economic; social; Constantine